Effect of the Radiation Flux on the Photocatalytic Inactivation of Spores of Bacillus Subtilis - Zacarias, Silvia Mercedes (2010)
In this paper, the photocatalytic inactivation of dry spores of Bacillus subtilis dispersed on TiO2 films and irradiated with UV-A radiation (2.44–0.29mWcm-2) was studied. Experimental results indicate a minor reduction in the number of viable spores (69% of inactivation after 48 h of irradiation) when they were irradiated with UV-A radiation on borosilicate glass plates (without TiO2), confirming the resistance of spores to UV-A radiation. However, the number of viable spores significantly decreased when they were irradiated with UV-A under similar conditions but on plates coated with TiO2 (99.88% of inactivation after 24 h of irradiation), showing that dry spores of B. subtilis are vulnerable to photocatalytic inactivation. A simplified scheme was proposed to model the photocatalytic inactivation of B. subtilis, from which a kinetic expression was derived. Since the rate of photocatalytic inactivation is strongly dependent on the flux of the UV radiation on the TiO2 films, the radiation field was modeled by means of CFD software. Experimental results of spore inactivation were fitted with the derived kinetic expression, showing the inactivation rate has a square root dependence on the radiation flux reaching the photocatalyst film.